Myth and Usability in the Zhuangzi’s “Wandering at Ease” - Sondaitė, Rima (Acta Orientalia Vilnensia, 2000)
The Book of Zhuangzi, a Chinese philosophical text, has a long interpretative tradition. This article deals with the problem of method in the Zhuangzi. The stories of the first Chapter “Wandering At Ease” are analysed with the aim to examine the connection between Zhuangzi’s method and contents. The detailed analysis of the main conceptions in Zhuangzi’s philosophy, such as (wu) hua (transformation), you (transcendental wandering), wu yong (uselessness), is given. It is argued that Zhuangzi’s theory of language is a key for understanding the lesding concepts in The Book of Zhuangzi as well as his philosophy’s existential character.